Injuries and Illnesses in the Preparticipation Evaluation Data of 1693 College Student-Athletes. (June 2015) - Matheson, Gordon O.; Anderson, Scott; Robell, Kevin
Background: While the preparticipation evaluation (PPE) is widely used by medical practitioners, its overall effectiveness is unknown, in part because there are no standardized or centralized mechanisms to collect and analyze medical history information. Purpose: To report on the injuries and illnesses identified with the use of an electronic PPE (ePPE) completed by first-time National Collegiate Athletic Association Division 1 varsity sport participants (N = 1693; 797 women, 896 men) upon entry to a single institution between 2010 and 2013. Study Design: Cross-sectional study; Level of evidence, 3. Results: In total, 3126 discrete past injuries were reported (women, 1473 injuries; men, 1653 injuries). Time loss from sport participation averaged 31.4 days for each injury (women, 32.2 days; men, 30.7 days), and aggregate time loss from sport for all student-athletes before the ePPE was 256 years. Eleven percent of student-athletes had injuries that were unresolved and still symptomatic at the time of the ePPE. Thirty percent of injured student-athletes had a history of ≥1 surgeries for an injury (women, 176; men, 213), and these accounted for 57% of the time lost from sport before college participation. Head injuries accounted for 9% (110 women, 173 men), and loss of consciousness was reported in 19% of these. One in 3 student-athletes answered "yes" to ≥1 of the American Heart Association questions on cardiovascular health. While 15% of women reported a history of stress fracture, only 3% reported a diagnosed eating disorder. Conclusion: While some data in this population are self-evident, we were not aware of the high frequency of past injuries, the magnitude of time lost from sport, the high frequency of past surgery, and the number of participants still symptomatic from injuries. The ePPE is a valuable tool for collecting and analyzing aggregate injury and illness data in athletes, such as the finding that 11% of injuries that were reported were unresolved and still symptomatic.